2009
DOI: 10.1128/cvi.00121-09
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Gamma Interferon, Tumor Necrosis Factor Alpha, and Interleukin-10 Gene Polymorphisms to Susceptibility to Mediterranean Spotted Fever

Abstract: The acute phase of Mediterranean spotted fever (MSF) is characterized by dramatic changes in cytokine production patterns, clearly indicating their role in the immunomodulation of the response against the microorganism, and the differences in cytokine production seem to influence the extent and severity of the disease. In this study, the single nucleotide polymorphisms (SNPs) of tumor necrosis factor alpha (TNF-␣) ؊308G/A (rs1800629) and interleukin-10 (IL-10) ؊1087G/A (rs1800896), ؊824C/T (rs1800871), and ؊59… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…Our results support some studies’ results which found that the number of TT genotype individuals was significantly elevated when compared to TA genotype subjects . Bouzgarrou et al .…”
Section: Discussionsupporting
confidence: 92%
“…Our results support some studies’ results which found that the number of TT genotype individuals was significantly elevated when compared to TA genotype subjects . Bouzgarrou et al .…”
Section: Discussionsupporting
confidence: 92%
“…274, 275 Nonetheless, even in an environment so different from that in which humans evolved, multiple studies have identified associations between patterns of increased inflammation observed in MDD and improved outcome in the context of infection, 3, 4, 5, 50, 276, 277, 278, 279, 280, 281, 282, 283, 284, 285, 286, 287, 288, 289, 290 as shown in Table 3.…”
Section: Patterns Of Immune Activation In Mdd and Protection From Infmentioning
confidence: 99%
“…Many variations within the IFN‐ γ gene have been shown to be associated with disease (Table ) . These associations may be related to expression of the IFN‐ γ gene.…”
Section: Ifn‐γ Genetic Variation and Diseasementioning
confidence: 99%